Pengaruh Audit Internal dan Pengendalian Internal terhadap Pencegahan Kecurangan (Fraud) pada Perusahaan di Kabupaten Karanganyar - Marshela Dwi Saputri; Rispantyo Rispantyo; Aris Eddy Sarwono; Sinta Putriana (Jurnal Ragam Pengabdian, 2026)
This study aimed to examine the effect of internal audit and internal control on fraud prevention in companies in Karanganyar Regency. The study employed a quantitative approach using primary data collected through questionnaires distributed to 102 employees working in the finance, accounting, and internal audit departments of companies in Karanganyar Regency. Respondents were selected using a purposive sampling technique, and the data were analyzed using multiple linear regression analysis to examine both the partial and simultaneous effects of the independent variables on fraud prevention. The results indicated that internal audit did not have a significant effect on fraud prevention (t = 0.837; p = 0.405), whereas internal control had a positive and significant effect (t = 4.407; p < 0.001). Simultaneously, both variables significantly influenced fraud prevention (F = 15.307; p < 0.001). Furthermore, the Adjusted R² value of 0.221 indicated that internal audit and internal control jointly explained 22.1% of the variation in fraud prevention, while the remaining 77.9% was influenced by other factors outside the scope of this study. These findings suggest that effective internal control plays a more important role in strengthening fraud prevention efforts within organizations than internal audit. Therefore, companies are expected to continuously improve the effectiveness of their internal control systems while enhancing the implementation of internal audit functions to support more effective fraud prevention and strengthen organizational governance.